FEATURES OF MANIFESTATION OF PSYCHOLOGICAL ALIENATION OF TEENAGERS IN THE CONDITIONS OF THREATS OF PSYCHOLOGICAL SAFETY LOSS - Mkrtumyan , M.P. (Modern Psychology, 2020)
In the article social and psychological determinants of psychological alienation and its manifestation in different conditions of activity are discussed. Mechanisms and psychophysiological regularities of behavioural changes of psychological alienation and the loss of psychological safety are revealed.
Keywords: psychological alienation; psychological safety; disadaptation; emotional instability; psychological vulnerability